(untitled) (IJM: Journal of Multidisiplinary, 2024)
Islamic Counseling Guidance (BKI) is a key profession that provides support to individuals facing problems, helps them return to Islamic teachings (fitrah), and faces opportunities and challenges in the era of Industrial Revolution 4.0. Advances in information technology have facilitated changes and developments in human life patterns. However, various psycho-social and public health issues (such as drug abuse) also arise. BKI exists as a solution to these challenges, with improvements in services, techniques, and strategies designed to solve individual problems and meet the needs of society. Islamic guidance and counseling must be at the forefront because it is able to increase adolescent maturity, develop self-potential, and self-actualization and prepare adolescents to have skills that are in accordance with the challenges of the times. In the Digitalization Era, adolescents experience changes both physical, spiritual, mind, emotional turmoil based on social role conflicts. This research approach is a qualitative approach, namely the Inquiry strategy that emphasizes the search for meaning, understanding, concepts, characteristics, symbol symptoms, and descriptions of a phenomenon and; focused and multimethodical, natural and holistic; prioritizing quality, using several ways, and presented narratively.